2012
DOI: 10.1158/0008-5472.can-11-2975
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response Is an Important Aspect of the Antitumor Effect Produced by a CD40L-Encoding Oncolytic Adenovirus

Abstract: Oncolytic adenovirus is an attractive platform for immunotherapy because virus replication is highly immunogenic and not subject to tolerance. Although oncolysis releases tumor epitopes and provides costimulatory danger signals, arming the virus with immunostimulatory molecules can further improve efficacy. CD40 ligand (CD40L, CD154) induces apoptosis of tumor cells and triggers several immune mechanisms, including a Thelper type 1 (T H 1) response, which leads to activation of cytotoxic T cells and reduction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
168
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(174 citation statements)
references
References 44 publications
5
168
0
1
Order By: Relevance
“…However, the observation that the tumor microenvironment tends to be pro-oxidative 63 implies that a therapeutic approach using antioxidants to decrease ROS production would be favorable to stimulate antitumor immunity. Importantly, many anticancer agents, including chemotherapy, 30 radiation, 22 or oncolytic viruses, 9,64,65 have been shown to induce HMGB1 release from cancer cells, highlighting the significance of further addressing the mechanism of how these modalities affect the redox status of HMGB1.…”
Section: Hmgb1mentioning
confidence: 99%
See 3 more Smart Citations
“…However, the observation that the tumor microenvironment tends to be pro-oxidative 63 implies that a therapeutic approach using antioxidants to decrease ROS production would be favorable to stimulate antitumor immunity. Importantly, many anticancer agents, including chemotherapy, 30 radiation, 22 or oncolytic viruses, 9,64,65 have been shown to induce HMGB1 release from cancer cells, highlighting the significance of further addressing the mechanism of how these modalities affect the redox status of HMGB1.…”
Section: Hmgb1mentioning
confidence: 99%
“…70 We and others recently showed that oncolytic viruses induce secretion of extracellular ATP from human cancer cells (Figure 1). 9,65 Unlike ecto-CRT induction, the release of ATP and HMGB1 is triggered by a range of death-inducing stimuli, and is not restricted to induction in apoptotic cell death. 47 Although ATP production is required for efficient vaccinia virus production 71 and facilitates HIV infection through its interaction with P2Y2 receptors, 72 there is little knowledge of how oncolytic viruses provoke ATP release.…”
Section: Adenosine Triphosphatementioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, adenovirus alone is not potent enough to initiate a powerful vaccine effect thus presenting the rationale for arming them with immunostimulatory molecules such as CD40L, a potent stimulator of dendritic cells (DCs). [4][5][6][7] There are more than 50 identified serotypes of adenoviruses. Serotype 5 adenoviruses (Ad5) are commonly used in gene therapy applications.…”
Section: Introductionmentioning
confidence: 99%